The Effect of Gadget Use on Student Social Behavior Patterns at SMA Negeri 3 Salatiga - Egi Des Fitria; Nani Mediatati (Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
The development of information and communication technology has increased the use of gadgets among high school students. Gadgets provide convenience in the learning process, but also have the potential to affect students' social behavior patterns. This study aims to describe and analyze the influence of gadget use on the social behavior patterns of students at SMA Negeri 3 Salatiga. This study uses a mixed methods approach, which is a combination of qualitative and quantitative methods. Qualitative data was obtained through observation, interviews, and documentation, while quantitative data was obtained through the distribution of questionnaires to 72 students in grades XI-5 and XI-7 who were selected using purposive sampling techniques. The results of the study showed that the use of gadgets had an effect on decreasing the intensity of direct social interaction, reduced empathy for the surrounding environment, weakening interpersonal communication with peers and teachers, and low cooperation in group activities. Students tend to focus more on the use of gadgets than active involvement in social activities in the school environment. Therefore, it is necessary for schools, teachers, and parents to supervise and guide the use of gadgets wisely so as not to hinder students' social development.